Understanding merchant adoption of m-payments in South Africa - Kalan, Anesh (Department of Computer Science, 2017)
Despite the proliferation of mobile communication technology and smartphone adoption, a number of barriers, most notably trust and security, and the lack of critical mass, have slowed the uptake of mobile payments (m-payments). Little is understood about the factors driving the success of novel, intermediating technologies such as m-payments, particularly in emerging markets. In this thesis, we empirically investigated the factors that affect the success of m-payments in Cape Town, from the merchant's perspective. The research model is based on the Perceived Characteristics of Innovation (PCI) instrument developed by Moore and Benbasat (1991) which measures an individual's perception of adopting m-payments. Our results found the main adoption drivers to be relative advantage, ease of use, results demonstrability, convenience, speed of transaction, and service provider brand value. The key barriers to adoption include cost as well as trust and security. Based on our findings, implications for practice and future studies are suggested.